The effect of scaffolding techniques on the ability of student’s reasoning ability and mathematics anxiety reviewed from gender - Sofiatun, Siti; Sampoerna, Pinta Deniyanti; Hakim, Lukman El (Unnes Journal of Mathematics Education, 2018)
The research conducted in Madrasah Aliyah Negeri (MAN) Insan Cendekia Serpong with quasi-experimental design aims to find out the effect of scaffolding technique on students’ ability of mathematical reasoning (KPM) and mathematical anxiety (KM) viewed from gender. The research sample is class X of science students (MIPA) which consist of 87 students; 41 male and 46 female obtained by cluster random sampling technique. The research data was obtained from the KPM test result and KM questionnaire filling and processed with two-track anava and t-test to answer the research hypothesis. The findings of this research are: (1) students’ KPM who were taught with scaffolding technique is higher than the conventional; (2) there is no interaction between learning techniques and gender to KPM; (3) KPM of male students who were taught with scaffolding technique is higher than the conventional; (4) there is no difference of KPM between group of female students who were taught with scaffolding and conventional technique; (5) there is no difference of KM between group of students who were taught with scaffolding and conventional technique; (6) there is no interaction between learning techniques and gender to student’s KM; (7) there is no difference of KM between male students who were taught with scaffolding and conventional technique; (8) there was no difference of KM between female students who were taught with scaffolding and conventional technique.